Ancient China - Cotterell, Arthur; Hills, Alan; Brightling, Geoff (New York : DK Publishing, 2005)
Illustrations and text explore the history of Imperial China from its earliest beginnings to the days of the last emperor.
World's oldest empire -- Beginning of China -- Teachings of Confucius -- Art of war -- First emperor of China -- In the empire's service -- Land of invention -- Paper, printing and books -- Three ways -- Health and medicine -- Three perfections -- Life in the fields -- Great waterways -- Within the city walls -- At home -- Food and drink -- Dressed for best -- Adornment -- Festivals and games -- Living in harmony -- Gardens of Heaven -- Arts and crafts -- Silk road -- Great ocean voyages -- End of the empire -- Did you know? -- Timeline -- Find out more -- Glossary -- Index.
Includes bibliographical references (pages 68) and index.
Keywords: China -- Civilization -- Juvenile literature